Foreign Investment in India: Pain or Panacea? - A Study With Reference to BSE and NSE - K. B., Nidheesh (Indian Journal of Finance, 2008)
Indian stock market opened to Foreign Institutional Investors in 14th September 1992, initially with lot of restrictions. The regulation on them are liberalized and minimized now, since 1993 has received a considerable amount of portfolio investment from foreigners in the form if FIIs investment in equities. This has become a turning point of India stock market. The government of India announced the policy of the government to permit the FII investment in India capital market. The objective of the study were ;To study the role of FII investment in the Indian stock market;To examine the causal relationship between net FII investment and BSE sensex using granger causality test ;To examine the causal relationship between net FII investment and NSE sensex using granger causality test ;To examine whether FIIs were a channel of global disturbance into the Indian stock market. The liberalization policies had the desired expansionary effect and had either increased the mean level of FII inflows and/or the sensitivity of these flows to a change in BSE returns and/or the inertia of these flows. On the other hand, the restrictive measures aimed at achieving greater control over FII flows also did not show any significant negative impact on the net inflows, it had found that these policies mostly render FII investment sensitive to the domestic market returns and raise the inertia of the FII flows.